2009
DOI: 10.1111/j.1365-2109.2008.02143.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fishmeal replacement withArtemiabiomass as a protein source in practical diets for the giant freshwater prawnMacrobrachium rosenbergii

Abstract: A 30-day feeding experiment was conducted in160-L plastic tanks to evaluate the potential use of Artemia biomass as a protein source in practical diets for postlarval Macrobrachium rosenbergii (initial mean weight of 12.12^12.29 mg). Nine isoenergetic and isonitrogenous experimental diets (approximately 40% crude protein) were formulated by replacing levels of the ¢shmeal (FM) protein di¡erence either with dried or frozen Artemia (0, 25, 50, 75 and 100%). The 0% Artemia treatment, in which Peruvian FM was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
2
12
1
2
Order By: Relevance
“…Weight in week 2 (g) 9.2 9.9 10.0 8.6 10. environment indicated that these prawn complemented their external FI with intakes of biofloc and that this had a high nutritional value for the prawn. This observation is supported by the study of Anh, Hien, Mathieu, Hoa, and Sorgeloos (2009), who report that use of Artemia biomass as fishmeal replacer in the diet to M. rosenbergii stimulated growth and improved survival. In addition, Asaduzzaman, Salam, Wahab, Kunda, and Rahman (2006) showed that carbohydrate addition to the water column of freshwater prawn nursery ponds increase the heterotrophic bacterial population and also reduced the levels of potentially toxic NH 3 -N, NO 2 -N in the water, without compromising the growth performance and survival of prawn postlarvae.…”
Section: Sem P-valuesupporting
confidence: 55%
“…Weight in week 2 (g) 9.2 9.9 10.0 8.6 10. environment indicated that these prawn complemented their external FI with intakes of biofloc and that this had a high nutritional value for the prawn. This observation is supported by the study of Anh, Hien, Mathieu, Hoa, and Sorgeloos (2009), who report that use of Artemia biomass as fishmeal replacer in the diet to M. rosenbergii stimulated growth and improved survival. In addition, Asaduzzaman, Salam, Wahab, Kunda, and Rahman (2006) showed that carbohydrate addition to the water column of freshwater prawn nursery ponds increase the heterotrophic bacterial population and also reduced the levels of potentially toxic NH 3 -N, NO 2 -N in the water, without compromising the growth performance and survival of prawn postlarvae.…”
Section: Sem P-valuesupporting
confidence: 55%
“…Linear regression analysis revealed that when the dietary Artemia protein inclusion level increased from 0 to 100%, the total feed intake and growth rate of goby increased significantly (P < 0.05); the greatest feed intake and the best growth performance occurred at 100% replacement of FM protein by Artemia protein. This result was similar to the result obtained for postlarvae of the freshwater prawn Macrobrachium rosenbergii (Anh et al 2009b).…”
supporting
confidence: 93%
“…2002). Furthermore, dried Artemia is a well‐suited feed for postlarval Litopenaeus vannamei shrimp (Naegel & Rodriguez‐Astudillo 2004) and for postlarval prawn, Macrobrachium rosenbergii (Anh et al. 2009).…”
Section: Introductionmentioning
confidence: 99%